1990
DOI: 10.1128/aem.56.6.1882-1889.1990
|View full text |Cite
|
Sign up to set email alerts
|

The bacteriophage kh receptor of Lactococcus lactis subsp. cremoris KH is the rhamnose of the extracellular wall polysaccharide

Abstract: A receptor for bacteriophages of lactic acid bacteria, including Lactococcus lactis subsp. cremoris KH, was found on the cell wall and not on the cell membrane, as determined by a phage-binding assay of sodium dodecyl sulfate-and mutanolysin-treated cell walls. The cell wall carbohydrates of L. lactis subsp. cremoris KH were analyzed by gas chromatography and mass spectrometry and found to contain rhamnose, galactose, glucose and N-acetylglucosamine. Similar analysis of mutants that were reduced in the ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(53 citation statements)
references
References 36 publications
2
51
0
Order By: Relevance
“…In a number of lactococcal phage/host systems, phage adsorption has been shown to involve attachment of the phage to a carbohydrate moiety in the cell wall, such as galactose and/or rhamnose and to a lesser extent glucose (Keogh & Pettingill, 1983;Valyasevi et al, 1990Valyasevi et al, , 1995Monteville et al, 1994). For phage c2, the primary adsorption step was found to be reversible, whereas the following binding to a receptor in the cell membrane was found to be irreversible (Valyasevi et al, 1991;Monteville et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of lactococcal phage/host systems, phage adsorption has been shown to involve attachment of the phage to a carbohydrate moiety in the cell wall, such as galactose and/or rhamnose and to a lesser extent glucose (Keogh & Pettingill, 1983;Valyasevi et al, 1990Valyasevi et al, , 1995Monteville et al, 1994). For phage c2, the primary adsorption step was found to be reversible, whereas the following binding to a receptor in the cell membrane was found to be irreversible (Valyasevi et al, 1991;Monteville et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…However, Sijtsma et al [7] showed that ConA reduced phage binding ability of L. lactis subsp, cremoris SKl12 essentially. Similarly, phage adsorption efficiency of L lactis subsp, cremoris KH [4] was considerably affected by the presence of the lectin from Momordica charantia (specific for n-galactose). These different responses of lactococcal cells and cell walls reflect strain specific differences in carbohydrate components participating in phage receptor structures.…”
Section: Resultsmentioning
confidence: 99%
“…They found phage binding to cell walls and, in one case, to the cytoplasmatic membrane of N-streptococci [3]. Recently, Valyasevi et al [4] reported that adsorption of five phages to L. lactis subsp. cremoris KH was significantly inhibited by Lrhamnose.…”
Section: Introductionmentioning
confidence: 99%
“…Cell walls were prepared according to the method of Valyasevi et al (1990). Cell walls (0.1 mg) were mixed with 0.1, 0.05 and 0.025 mg lectins from concanavalin A (Con A), Vicia sativa, Momordica charantia and Bandeiraea simplificifolia (Sigma Chemical Co., St Louis, MO, USA) in a final volume of 1.0 mL of 50 mM Tris-HCl, pH 6.8, and incubated for 20 min at 25°C.…”
Section: Preparation and Lectin Treatment Of Cell Wallsmentioning
confidence: 99%